Mapeamento da cadeia de suprimentos em empresa do ramo de plásticos de performance - Alencar, Thales Henrique Moura (Universidade Federal de São Carlos, 2020)
Due to the increasing market transformations that we have been going through, companies need to keep up by being agile and innovative. Knowing and controlling the value chain is essential to keep them competitive in the market. Therefore, the objective of this work was to map the value chain from a company in the performance plastic segment, more precisely, in the non-stickpolytetrafluoroethylene (PTFE) covered fabric, detailing the process using Value Stream Mapping (VSM). This work is divided in two parts: the first one is a contextualization of the lean manufacture and the exploration of the VSM tool and the second one is a field application of the framework. Through mapping, it is possible to verify the process in which an order is transformed into a product, visualizing the current process performance and highlighting the future opportunities of improvements in the chain. From the construction of the VSM in the future state, the suggested projection showed a reduction of 51% of the current lead time, with the Work-in-Process (WIP) reduced by 80%, leading to a 108% improvement in value added.
Supply Chain Mapping in a Performance Plastics Company
Keywords: Mapeamento de fluxo de valor; Cadeia de suprimentos; Produção enxuta; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA